THE VIEWS OF THE TOURISM VILLAGE MANAGERS ON THE GREEN EVENT CONCEPT IN BALI - Christantius Dwiatmadja; I Putu Astawa; Tjokorda Gde Raka Sukawati (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2019)
Green event remains an issue under debate in the effort to support sustainable tourism today, because the result of the previous research has not found a standard model for the implementation of the green event concept. This research describes the views of the village tourism managers on the green event model developed by the Bali State Polytechnic. Green events are developed on the basis of two aspects: green and cultural aspects. Data were collected through questionnaires sent by email and by post to village tourism managers. There are a hundred tourist villages planned to be developed in Bali and all are made research samples. The collected data were analyzed by using descriptive statistics. The results of the study indicate that the understanding of green aspects includes green foods, waste management, natural materials, and ecosystem is averagedly quite good. The result of the analysis from the cultural aspect is very good, meaning that the culture practised by the community gives a strong impetus to keep the environment sustainable so that the harmonious relationship with nature, humans, and God is maintained through the activities in Tourism Villages. Other results indicate that an understanding related to the ecosystem, the green food, and the waste management needs a special attention to further improve understanding. Green event as an alternative product in supporting the tourist village is very much expected by the managers that will further be synergized with the existing culture. The combination of both green event and existing culture is quite unique and will constantly keep the concept of sustainable tourism. These findings give a contribution to the theory of green tourism or sustainable tourism which is built upon the event and based on the blend of modern and traditional concepts. Keywords: green event, sustainable tourism, tourism village, culture